Lecture Notes on Composite Materials - Borst, René de (Springer, 2017)
The text gives a modern, up-to-date account of recent developments in the modelling of composite materials. Multiscale concepts, which are the new paradigm in (computational) mechanics, are at the heart of this text, and are treated in detail in the first three chapters of the book. Other relevant developments are covered in the later chapters of the book, beginning with the most relevant issue of coupling stress analysis and diffusion phenomena that arise from hygral and/or thermal loading, which are of crucial importance of the short and long-term resistance of composite materials. The volume facilitates understanding of the basic principles of damage growth and fracture processes in various composite materials, including ceramics, polymers, metal-matrix composites and porous materials.